Performance of trust-based governance - Bart S. Vanneste; Onesun Steve Yoo (Journal of Organization Design, 2020)
Trust is crucial for the success of interorganizational relationships, yet we lack a clear understanding of when trust-based governance is likely to succeed or fail. This paper explores that topic via a closed-form and a computational analysis of a formal model based on the well-known trust game. We say that trust-based governance performs better in situations where it results in a willingness to be vulnerable with trustworthy others and an unwillingness to be vulnerable with untrustworthy others. We find that trust-based governance performs better in situations in which (a) trustworthy and untrustworthy partners exhibit markedly different behavior (high behavioral risk) or (b) the organization is willing to be vulnerable despite doubts concerning the partner's trustworthiness (low trust threshold).
Keywords: 650; Trust-based governance; Trust game; Interorganizational relationships